การกักเก็บน้ำหอมโดยใช้โซเดียมไตรโพลีฟอสเฟตและแป้งดัดแปรสำหรับผงซักฟอก - ธีราพัฒน์ บุญชัยพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
Fragrance plays an essential role in detergents, serving both aesthetic and marketing functions.  In traditional detergent manufacturing, liquid perfume is incorporated, introducing moisture and the risk of clumping if excessive.  To address this concern, perfume in powder form has been introduced, notably utilizing melamine-formaldehyde as an encapsulant.  However, the environmental release of microplastics remains a drawback.  In response to this issue, various encapsulating materials have been investigated, including the focus of this research, which aims to establish guidelines for perfume powder using the spray drying technique.  Sodium tripolyphosphate (STPP) and HI-CAP® 100 (HICAP) were chosen as wall-materials, with D-limonene (DL) as a model perfume, maintaining a solid content of 21%, and a Core/Wall Ratio of 0.2.  The production of perfume powder involves two key steps: emulsion preparation and spray drying.  The experimental manipulation of the STPP:HICAP ratio during emulsion preparation revealed that a 1:1 ratio is sufficient for effective DL encapsulation.  However, the method of adding STPP affected emulsion particle size distribution, while HICAP contributed to enhanced emulsion combination.  Additionally, varying the Inlet Temperature during the spray drying process demonstrated its impact on DL content on surface, and moisture content in the perfume powder.  The morphology of the perfume powder revealed distinct surface characteristics, indicating varying DL concentrations.  Moreover, the stability of the perfume powder was assessed over 21 days.  However, detergent formulations with a higher HICAP content exhibited more pronounced deterioration characteristics.  This research provides valuable insights into optimizing the encapsulation of perfume in detergent powders, contributing to both aesthetic and functional aspects.